FORMULASI TABLET HISAP EKSTRAK RIMPANG LENGKUAS (Alpinia galanga (L.) Swartz ) DENGAN VARIASI JUMLAH BAHAN PENGIKAT GELATIN - , NUR HAWWIN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Galangal rhizome (Alpinia galanga (L.) Swartz) is a plant that is used for medication, one of the properties is as a tonic (Yuliani, et al., 2008). Development of dosage forms needed to improve acceptability. Lozenge dosage forms have been practical and comfortable consumed. Lozenges having a high hardness. These properties are affected by the use of a binder agent. The purpose of this study was to determine the effect of variations in the levels of gelatin binder on the physical properties of galangal rhizome extract lozenges. Galangal rhizome extract was made by maceration method. Crude extract was tested with organoleptic test, adhesion test, viscosity test, and its drying shrinkage. Galangal rhizome lozenges made in 4 formula with gelatin binder content variation (0%, 0.5%, 1.0% and 1.5% of the weight of the tablet) by wet granulation method. Gelatin was added in the form of a solution of 10% w / v. The resulting granules were dried and tested for its flow time and compactibility. Lozenges was tested for its weight uniformity, friability, dissolution rate and taste responsiveness. The data obtained were analyzed by one way ANOVA level of 95% followed by LSD (Least Significant Difference). the formula D that generated by using a gelatin binder content of 1.5% was chosen as the best formula because of its physical properties that most qualified. Increased levels of binder causes increased granule compactibility, tablet hardness and dissolution time of the tablet while lowering the flow properties of granules and tablets fragility.